N—H...O, O—H...O hydrogen‐bonded supramolecular sheet formation in the bis(2‐aminoanilinium) fumarate, 3‐methylanilinium hydrogen fumarate and 4‐chloroanilinium hydrogen fumarate salts. (12th July 2013) - Sathya, D.; Jagan, R.; Padmavathy, R.; Kumar, R. Mohan; Sivakumar, K.
<x xml:space="preserve">Abstract</x> In bis(2‐aminoanilinum) fumarate, 2C6H9N2+·C4H2O42−, (I), the asymmetric unit consists of two aminoanilinium cations and one fumarate dianion, whereas in 3‐methylanilinium hydrogen fumarate, C7H10N+·C4H3O4−, (II), and 4‐chloroanilinium hydrogen fumarate, C6H7ClN+·C4H3O4−, (III), the asymmetric unit contains two symmetry‐independent hydrogen fumate anions and anilinium cations with a slight difference in their geometric parameters; the two salts are isostructural. In (II) and (III), the carboxylic acid H atoms of the anions are disordered across both ends of the anion, with equal site occupancies of 0.50. Both the 4‐chloroanilinium cations of (III) are disordered over two orientations with major occupancies fixed at 0.60 in each case. The hydrogen fumarate anions of (II) and (III) form one‐dimensional anionic chains linked through O—H...O hydrogen bonds. Salts (II) and (III) form two‐dimensional supramolecular sheets built from R44(16), R44(18), R55(25) and C22(14) motifs extending parallel to the (010) plane, whereas in (I), an (010) sheet is formed built from two R43(13) motifs, two R22(9) motifs and an R44(18) motif.